Mexican Pharmacies and Antibiotic Consumption at the US-Mexico Border - Homedes, Núria (Dr. Zaheer-Ud-Din Babar, 2012)
Objective: To study antibiotic dispensing to US and Mexican residents, at Mexican pharmacies at the US-Mexico border, and the pharmacy clerks’ capability to promote appropriate use. Methods: The site selected was Ciudad Juarez, Chihuahua (pop. 1.2 million) separated from El Paso, Texas (pop. 800,000) by the Rio Grande River. A convenience sample of 32 pharmacies located near the international bridges, major shopping centers, and interior neighborhoods was selected. Pharmacy clients were interviewed (n=230) and 152 interactions between clients and pharmacy clerks were observed. Information was obtained about education and pharmaceutical training of 113 clerks working in 25 pharmacies. A senior pharmacy clerk in each of the 25 pharmacies was interviewed and asked for their recommendations to clients presenting two clinical scenarios and seven diagnoses. Findings: Professionally trained pharmacists only spend a few hours a week in some pharmacies. Clerks’ education levels are very low; some have only completed primary education. There is no required pharmaceutical training and their knowledge about pharmaceuticals comes mostly from representatives of the pharmaceutical industry. Clerks’ knowledge of antibiotics, the most frequently sold class of medicines (65% without prescription), is very limited. Clients trust pharmacy clerks and tend to follow their advice. Conclusions: The findings raise concerns about dispensing of antibiotics at Mexican border pharmacies and antibiotic overuse due to lack of control. Because inappropriate antibiotic use contributes to increased resistance, pharmacy clerks should receive independent training to dispense antibiotics and promote their appropriate use.